The Role Model of MICE Activities After the COVID-19 Pandemic in Indonesia - Syah, Firman; Rajoendah, Muhammad Iqbal Katik (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2022)
This quantitative research applying SmartPLS3 aimed to look at the overall existing problems in the field related to the impact of the COVID-19 pandemic on MICE business actors and the hybrid model on the existence of MICE activities in Indonesia. The focus of the research was only five representative cities that are the target of MICE activities based on the government’s plan, including Jakarta, Bogor, Bali, Yogyakarta, and Malang. Considering that it has been a year since the COVID-19 pandemic ravaged countries in the world, especially in Indonesia, it brought its own problems. One of the sectors affected is tourism and MICE, and even worse, not a few business actors have given up. They finally switched professions in the fields of culinary, agriculture, and plantations as an alternative business during the pandemic. The emergence of this hybrid concept makes business actors keep moving on. Several alternative solutions prepared during the COVID-19 pandemic include holding virtual MICE, virtual tourism, virtual events, webinars, as well as holding meetings via the Google Meet and Zoom Meet applications, as well as holding teleconferences. This means that the development of the MICE industry will continue to be carried out through the use of more intense technology. It is undeniable that this new activity requires creativity and high quality so that the virtual event can run well